TOLERANSI AGAMA DAN KEADILAN SOSIAL DI BOSNIA & HERZEGOVINA ERA PENGUASAAN ‘UTHMANIYYAH ABAD KE-15 HINGGA ABAD KE-17M (Religious Tolerance and Social Justice in Bosnia & Herzegovina during Ottoman era between 15th until 17th century AD) - Alias, Nur Ainul Basyirah; Rozali, Ermy Azziaty; Yahya, Shamsul Azhar (Journal of Al-Tamaddun, 2019)
Bosnia, which is located on the Balkan Peninsula is a territory under the rule of the Ottoman Empire since 1463. After that, local people began to assimilate with the systems, way of life and culture brought by them. However, the Ottoman ruler at that time, Sultan Mehmet II does not force non-Muslims to embrace Islam and they can still continue to practice their own religion and culture. Therefore, this study focuses about religious tolerance and social justice as practiced by Ottoman ruler in Bosnia between 15th century and 17th century. This is because that two centuries were the most significant classical age in the Ottoman Empire. This study was conducted using qualitative methods in the form of historical research and data collection methods used the method of analysis of documents using various primary and secondary sources. The study found that both aspects are taken by Sultan Mehmet II was opened up to Islam more recognizable and approachable. In fact, the number of local residents who converted to Islam has also increased. In addition, it is also an impact on the population of Bosnia to give loyalty and obedience to the Ottoman rulers. The study also shows that religious tolerance and social justice are reflected in the establishment of institutional endowments and grants the peace decree ‘Ahdname to local communities. As a conclusion, among the factors of success in the conquest of Bosnia and the spread of Islam in the 15th century is it’s receptive in terms of religion and upholding the concept of social justice in society.